Discordant phylodynamic and spatiotemporal transmission patterns driving the long-term persistence and evolution of human coronaviruses - Mah, Marcus G.; Zeller, Michael A.; Zhang, Rong; Zhuang, Yan; Maro, Venance P.; Crump, John A.; Rubach, Matthew P.; Ooi, Eng Eong; Low, Jenny G.; Wang, De Yun; Smith, Gavin J. D.; Su, Yvonne C. F. (Npj viruses, 2024)
Four distinct species of human coronaviruses (HCoVs) circulate in humans. Despite the recent attention due to SARS-CoV-2, a comprehensive understanding of the molecular epidemiology and genomic evolution of HCoVs remains unclear. Here, we employed primary differentiated human nasal epithelial cells for the successful isolation and genome sequencing of HCoVs derived from two retrospective cohorts in Singapore and Tanzania. Phylodynamic inference shows that HCoV-229E and HCoV-OC43 were subject to stronger genetic drift and reduced purifying selection from the early 2000s onwards, primarily targeting spike Domain A and B. This resulted in increased lineage diversification, coinciding with a higher effective reproductive number (R e >1.0). However, HCoV-NL63 and HCoV-HKU1 experienced weaker genetic drift and selective pressure with prolonged regional persistence. Our findings suggest that HCoV-229E and HCoV-OC43 viruses are adept at generating new variants and achieving widespread intercontinental dissemination driven by continuous genetic drift, recombination, and complex migration patterns.